2014
DOI: 10.1080/00405000.2014.952966
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of automated geometry modeling process of woven fabrics based on the yarn structures

Abstract: Fabric structure has a significant effect on the thermal protective performance of fabrics. Before studying the thermal performance of textiles by numerical methods, it is essential to create geometric models of textile structures. Common fabrics, such as plain weave, 2/1 twill, 3/3 twill, 5/3 satin, and double layer fabric, were modeled using TexGen software. To obtain the input data for geometry simulation of fabrics, geometric measurements were studied. Methods of modeling fabric geometries according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The fabric faces are shown in Figure 4. Zheng et al 19 worked out plain and various twill patterns for geometric modeling and indicated that the twill weave structure is less uniform than the plain.…”
Section: Fabric Geometrymentioning
confidence: 99%
“…The fabric faces are shown in Figure 4. Zheng et al 19 worked out plain and various twill patterns for geometric modeling and indicated that the twill weave structure is less uniform than the plain.…”
Section: Fabric Geometrymentioning
confidence: 99%
“…However, both carbon fiber and carbonized silicone resin had the irregular shape, and their volume could not be calculated accurately and thus calculated their density using the pycnometer method. The specific operation method of pycnometer method could be found in Zheng et al (2015):…”
Section: Definition Of Materials Propertiesmentioning
confidence: 99%
“…1. The path of yarn could be determined by weave pattern and geometric parameters in TexGen [16,17], and the cross-section shape of yarns was modified as ellipse proposed by Pierce * based on experimental images. This model can restore the real spatial distribution of yarns in fabric.…”
Section: Geometrical Modelmentioning
confidence: 99%